2018
DOI: 10.1038/cr.2018.14
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the human activated spliceosome in three conformational states

Abstract: During each cycle of pre-mRNA splicing, the pre-catalytic spliceosome (B complex) is converted into the activated spliceosome (Bact complex), which has a well-formed active site but cannot proceed to the branching reaction. Here, we present the cryo-EM structure of the human Bact complex in three distinct conformational states. The EM map allows atomic modeling of nearly all protein components of the U2 small nuclear ribonucleoprotein (snRNP), including three of the SF3a complex and seven of the SF3b complex. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
235
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(252 citation statements)
references
References 70 publications
(116 reference statements)
7
235
1
2
Order By: Relevance
“…A recently reported structure of human B act spliceosomes suggests that RNF113A joins the complex after U4 dissociation and is important for the complex rearrangements and activation. 35 All together, our data indicate that RNF113A joins the spliceosome either on B or B act intermediate complexes (Figure 4). Second, our results indicated that the addition of excess recombinant RNF113A led to splicing inhibition.…”
Section: Discussionsupporting
confidence: 52%
“…A recently reported structure of human B act spliceosomes suggests that RNF113A joins the complex after U4 dissociation and is important for the complex rearrangements and activation. 35 All together, our data indicate that RNF113A joins the spliceosome either on B or B act intermediate complexes (Figure 4). Second, our results indicated that the addition of excess recombinant RNF113A led to splicing inhibition.…”
Section: Discussionsupporting
confidence: 52%
“…These changes lead to release of some proteins and recruitment of others to the spliceosome, ensuring the fidelity and directionality of spliceosome assembly and catalysis (Koodathingal and Staley 2013). Recent cryo-electron microscopy (cryo-EM) models of spliceosomes at distinct steps (tri-snRNP, the A, B, B act , C, and P complexes) have brilliantly illuminated the composition and conformation of the spliceosome before and after each transition Yan et al 2015;Galej et al 2016;Rauhut et al 2016;Wan et al 2016;Yan et al 2016;Bai et al 2017;Bertram et al 2017a;Bertram et al 2017b;Liu et al 2017;Plaschka et al 2017;Wan et al 2017;Wilkinson et al 2017;Yan et al 2017;Zhang et al 2017;Plaschka et al 2018;Zhan et al 2018b;Zhan et al 2018a;Zhang et al 2018). A challenge now is to understand the distinct mechanism of action of each DExD/H protein in catalyzing its specific transition.…”
Section: Introductionmentioning
confidence: 99%
“…RNA splicing relies on the spliceosome and is a conserved and very large complex consisting of 5 small nuclear RNP (snRNP) complexes (U1, U2, U4, U5, and U6) and ;150 proteins (31). Several studies have demonstrated the resolution of the spliceosome complex by cryogenic electron microscopy structural analysis (32)(33)(34)(35)(36). The structural analysis revealed a number of striking features that advance our mechanistic understanding of exon ligation.…”
Section: Discussionmentioning
confidence: 99%